PENGARUH KOMBINASI TERAPI AKUPRESUR DAN PEMBERIAN JUS SIRSAK TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA GOUT ARTHRITIS - Yogi Utomo; Galih Setia Adi; Tresia Umarianti (Jurnal Ilmiah Maternal, 2018)
ABSTRACTGout arthritis is a disease caused by the accumulation of uric acid or uric monosodium crystalline in tissues,particularly in join tissues. Non-pharmacological management such as herbal therapy and complementary one isusually suggested to deal with it. A preliminary study conducted at Community Health Center of Banyudono Ishows that 64 (37.6%) of the clients there experienced hyperuricemia. The objective of this research is to investigatethe effect of the combination of acupressure therapy and soursop juice administration on the decrease of the goutarthritis sufferers’ uric acid level. This research used the quasi experimental research method with pre-test andpost-test with control group design. Its population was 64 clients in the work area of Community Health Center ofBanyudono I. Purposive sampling technique was used to determine its samples. The respondents of the researchbased on the Roscoe’s Theory 20: 10 in the treatment group and 10 in the control group. The result of the pairedt test to the treatment group shows that the p-value was 0.000 which was less than 0.05. Meanwhile, the result ofthe independent t test to the treatment group and control group shows that the p-value was 0.149 which wasgreater than 0.05. Thus, the combination of acupressure therapy and soursop juice administration had an effecton the decrease of uric acid level, but there was not any significant difference of effect of the acupressure therapyand the soursop juice administration between the treatment group and the control group on the decrease of uricacid level.Keywords: Acupressure, gout arthritis, soursop juice, uric acid levelABSTRAKPenyakit gout atau gout arthritis merupakan penyakit yang disebabkan oleh penumpukan asam urat atau kristalmonosodium urat (MSU) di jaringan, terutama jaringan sendi. Penatalaksanaan secara non farmakologi yang biasanyasering disarankan yaitu dengan terapi herbal dan terapi komplementer. Studi pendahuluan yang dilakukan penelitidi Puskesmas Banyudono I didapatkan data 64 (37,6%) warga mengalami hiperurisemia. Tujuan penelitian iniuntuk mengetahui pengaruh kombinasi terapi akupresur dan pemberian jus sirsak terhadap penurunan kadar asamurat pada penderita gout arthritis. Penelitian ini menggunakan desain quasy-experiment dengan pendekatan pretest and post test with control group. Populasi penelitian ini sebanyak 64 orang di wilayah kerja puskesmasBanyudono I. Teknik pengambilan sampel menggunakan Purposive Sampling. Jumlah responden pada penelitianini berdasarkan pada Roscoe sebanyak 20 responden, 10 responden sebagai kelompok perlakuan dan 10 respondensebagai kelompok kontrol. Hasil analisa uji paired t test  pada kelompok perlakuan didapatkan p value = 0,000 0,05. Sedangkan hasil analisa uji independen t test pada kelompok perlakuan dan kelompok kontrol didapatkan pvalue = 0,149 0,05. Kesimpulan dari penelitian ini adalah terdapat pengaruh kombinasi terapi akupresur danpemberian jus sirsak terhadap penurunan kadar asam urat dan tidak ada perbedaan bermakna pada kelompokperlakuan dan kelompok kontrol terhadap penurunan kadar asam urat.Kata Kunci: Akupresur, gout arthritis, jus sirsak, kadar asam urat